Creativity and intentionality: a philosophical attempt at reconstructing a creative process - Gondek, Paweł (Creativity Studies, 2021)
The paper presents a philosophical proposition of elucidating creativity by means of distinguishing the category of intentionality. The intentional dimension of cognitive content encompasses predispositions for constructing sign systems. Such an intellectual modification of sign systems forms the foundation of dynamic creative acts. However, creative processes are not restricted to the sphere of intellectual operations, but also remain under the influence of object categories. For this reason, the results of creative processes must allow for the potential determinants of sensual matter. A transition between the subjective sphere of possibility and the objective sphere of potency indicates the dynamism of the process. A crucial component of the emergence of intentional relations is formulating the criterion of a creative process. It determines the rules of constructing sign systems, the forms of acceptable transformations as well as the possible modes of allowing for the results of this process.